The Conflicted Juvenile Delinquency Court after Gault: A Qualitative Examination of Actors and Processes in Two Contemporary Courts. (2nd January 2018) - Pennington, Liana
ABSTRACT: The contemporary juvenile court aims to protect juveniles' due process rights and to address the social welfare of youth. The seminal case In re Gault (1967 ) requires juvenile court judges to make determinations of fact using standards resembling the adult criminal process. At the same time, the Supreme Court in Gault aimed to preserve a focus on the treatment and rehabilitation of adolescent offenders. Contemporary juvenile courts continue to have both adversarial and rehabilitative elements. While experts note the potential conflict between due process protections and social welfare objectives, little research has examined how, in practice, the balance is struck between these two goals in the contemporary juvenile court. This research examines the ability of two contemporary juvenile courts to provide constitutional protections while also responding effectively to youths' social welfare needs. By combining 106 observations of court hearings and attorney meetings with 86 interviews of parents and youth about their court experiences, this research finds substantial conflict between these two objectives. These two courts often fail to adequately address the individual needs of each child or to fully realize their due process function. Policy implications are discussed.